Análisis De Las Estrategias De Comunicación De La Campaña Fe En La Causa En El Batallón De Apoyo Y Servicios Para El Combate N°8 Cacique Calarcá De La Ciudad De Armenia (2013)
The present work consisted of realizing an analysis of the strategies of the campaign "Faith in the cause" in the Battalion of support and services for the combat No. 8 Cacique Calarcá from Armenia, linked to the eighth brigade and the National Army of Colombia, terrestrial legitimate armed force that operates in the Republic of Colombia. In agreement to the political constitution, his principal mission is the defense of the sovereignty, the independence, the integrity of the national territory and of the constitutional order, is constituted by different men and women and his maximum commander is the president of the Republic. As objective this project tried to realize an investigation of the impact and the level of persuasion that has the campaign "faith in the cause" in the sub-officials of the battalion previously mentioned, for it, one resorted to several documents and books that contain the topics to investigating and that reach in a forceful way to the interpretation of the cast results of interviews and surveys realized to the population to investigating.